Familial multiple sclerosis: case study of three affected siblings - Bencsik, K.; Rajda, C.; Seres, E.; Vörös, E.; Janáky, M.; Dibó, Gy; Járdánházy, T.; Vécsei, L. (Acta neurologica Scandinavica, 2002)
Bencsik K, Rajda C, Seres E, Vörös E, Janáky M, Dibó Gy, Járdánházy T, Vécsei L. Familial multiple sclerosis: case study of three affected siblings. Acta Neurol Scand 2002: 106: 392–395. © Blackwell Munksgaard 2002. We report on three sisters with new‐onset multiple sclerosis (MS). The symptoms of the eldest sister began in 1993 with lower‐limb weakness and paraesthesia. In 1998, she had limb weakness, nystagmus and ataxia. Magnetic resonance imaging (MRI) of the brain, the cerebrospinal fluid (CSF) examinations, and evoked potentials verified MS. The middle sister exhibited left‐side optic neuritis in 1998. All findings pointed to MS. The third sister had subjective complaints such as paraesthesias and vertigo. MRI and CSF results supported the diagnosis. Both parents and all four grandparents are without neurological signs; the brain MRI examinations on the parents were negative. The prevalence of familial MS in first‐degree relatives is 5–10%, while that in twins is 20–30%. In this case, environmental factors seem to play the crucial role. Although the anamnesis as concerns MS proved negative in the other family members examined here, further genetic examination of the sisters is needed.